Examining the relationship between corporate governance and bank performance in Bangladesh - J. Islam; S. Sathye; H. Hu (South African Journal of Business Management, 2015)
Previous research has studied the impact of corporate governance on bank performance, but only a few aspects of the impact were reported. The present study develops a unique corporate governance index to provide a comprehensivemeasure of corporate governance and examines the relationship between this comprehensive measure and bank performance. We apply the Wilcoxon signed rank test to examine whether the introduction of the Code of CorporateGovernance in Bangladesh has significantly promoted the improvement of corporate governance practices in Bangladeshi banks. Our results provide support for the hypothesis that corporate governance practices of Bangladeshi banks have been significantly improved since the introduction of the code. Further, the present study adopts regression analysis and reveals that the comprehensive measure of corporate governance is not significantly related to Bangladeshi banks' performance.
Keywords: 650